Acute idiopathic pericarditis: the importance of guideline-based treatment to avoid recurrence. (3rd October 2022) - Marcolongo, R; Giordani, A; Brunetti, M; Gregori, D; Lorenzoni, G; Iliceto, S; Baritussio, A; Caforio, A L P
Abstract: Background: Acute pericarditis (AP) usually resolves with first-line treatment, but it may recur. Recurrences are attributed to a deranged immunity, but it is unclear if they may also be related to inappropriate treatment. Purpose: The aim of our study was to clarify the potential role of inappropriate treatment on relapse episodes in AP. Methods: Consecutive patients prospectively followed-up over 20 years at Padua University Cardio-immunology outpatient clinic were included. Clinical and instrumental findings were recorded at diagnosis and at each follow-up. Spectrum, appropriateness, efficacy and side effects of therapies received by patients before and after referral to our centre were considered. The distribution of recurrence-free survival probability was estimated using Kaplan-Meier method; impact of the covariates of interest on the outcome was assessed using Cox univariate analysis models. Results: The study included 144 patients (57% male, mean age 50 years, 143 Caucasian and 1 African). 139 patients had AP, which was recurrent in 63; 5 had constrictive pericarditis. Etiology was idiopathic/presumed-viral in 112 patients, bacterial in 1, secondary to pericardial injury in 26, to Dressler syndrome in 2, and to a systemic immune-mediated disease in 3. At diagnosis, 68% were in NYHA class I; 9% developed cardiac tamponade; 84% received non-steroidal-anti-inflammatory drugs (NSAIDs), 54% colchicine and 19% corticosteroids. Treatment was not in line with ESC guidelines in 31% of patients for NSAIDs, in 12% for steroids and in 28% for colchicine, requiring readjustment. All patients with constrictive pericarditis underwent uncomplicated pericardiectomy. No patient was dead at last follow-up. Estimated recurrence-free-survival probability was 86% at 1st year, 58% at 5th, 52% at 10th. Variables which tended to be associated with a higher risk of recurrence were: cardiac tamponade at diagnosis, left heart failure, concomitant immune-mediated diseases, history of recurrence, inappropriate treatment with colchicine, inappropriate treatment with NSAIDs, III or IV NYHA class at diagnosis. Treatment of acute/recurrent forms before referral did not appear in line with the international recommendations in terms of daily dosage or duration, or both, in 43 patients for NSAIDs, in 17 for corticosteroids and in 39 for colchicine, which was omitted despite the absence of contraindications (Table 1). Following treatment adjustment to international guidelines, 107 patients with relapsing pericarditis obtained complete remission; only 13 (9%) of our AP patients showed a truly treatment-refractory form that required a second-line therapy. Conclusion: When treated according to international guidelines, pericarditis has usually a favorable course, even in its most adverse presentations. Treatment inaccuracies seems to account, at least in part, to disease recurrences. Funding Acknowledgement: Type of funding sources: None.